2024
DOI: 10.3847/1538-3881/ad11d9
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Complex Organic Molecules in the V883 Ori Disk Revealed by ALMA Band 3 Observations

Yoshihide Yamato,
Shota Notsu,
Yuri Aikawa
et al.

Abstract: Complex organic molecules (COMs) in protoplanetary disks are key to understanding the origin of volatiles in comets in our solar system, yet the chemistry of COMs in protoplanetary disks remains poorly understood. Here, we present Atacama Large Millimeter/submillimeter Array Band 3 observations of the disk around the young outbursting star V883 Ori, where the COMs sublimate from ices and are thus observable thanks to the warm condition of the disk. We have robustly identified ten oxygen-bearing COMs including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 146 publications
(225 reference statements)
0
0
0
Order By: Relevance
“…Generally, the D/H ratio of molecules (deuterium fractionation) reflects their formation processes as well as physical conditions and evolutionary stages. In fact, it has extensively been studied with observations of various deuterated species of not only CH 3 OH but also other molecules over the various regions, such as starless cores (e.g., Bizzocchi et al 2014;Ambrose et al 2021), both low-mass and high-mass protostars (e.g., Bianchi et al 2017aBianchi et al , 2017bJørgensen et al 2018;Taquet et al 2019;Manigand et al 2020;Drozdovskaya et al 2022;van Gelder et al 2022;Yamato et al 2024), andcomets (e.g., Drozdovskaya et al 2021;Müller et al 2022). In these studies, the D/H ratios toward low-mass protostars are found to reach up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the D/H ratio of molecules (deuterium fractionation) reflects their formation processes as well as physical conditions and evolutionary stages. In fact, it has extensively been studied with observations of various deuterated species of not only CH 3 OH but also other molecules over the various regions, such as starless cores (e.g., Bizzocchi et al 2014;Ambrose et al 2021), both low-mass and high-mass protostars (e.g., Bianchi et al 2017aBianchi et al , 2017bJørgensen et al 2018;Taquet et al 2019;Manigand et al 2020;Drozdovskaya et al 2022;van Gelder et al 2022;Yamato et al 2024), andcomets (e.g., Drozdovskaya et al 2021;Müller et al 2022). In these studies, the D/H ratios toward low-mass protostars are found to reach up to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…The values were found to be comparable with the local interstellar medium (ISM) value ( 12 C/ 13 C = 68; Milam et al 2005) or to show lower 12 C/ 13 C ratios toward source B (Jørgensen et al 2016(Jørgensen et al , 2018, which are consistent within the error with the local ISM value for source A (Manigand et al 2020). In the Class I low-mass young outbursting star V883 Ori, COMs are enriched in 13 C ( 12 C/ 13 C ∼20-30) (Yamato et al 2024).…”
Section: Introductionmentioning
confidence: 99%